Efektifitas Back Massage terhadap Produksi ASI pada Ibu dengan Post Sectio Caesarea - Grasiana Florida Boa; Maria Christina Endang S; Petrus Belarminus (JURNAL KESEHATAN PRIMER, 2021)
Abstract: Introductions: Production of little or no fluent milk in the first days of childbirth becomes an obstacle in breastfeeding for mothers with post-sectio caesarea. Back Massage is an alternative solution to overcome the smooth production of breast milk. The purpose of this study was to see the effectiveness of Back Massage on the production of breast milk in mothers with cesarean post section. Methods: This study design used two groups of pre-post-test designs. The population of this study was all 22 post-sectio Caesarea patients in the Midwifery room of the Waikabubak Regional Hospital. The research instrument used a questionnaire, indicator guidelines, and observation sheets. T-test data analysis for bivariate data. Results: The results showed that back massage interventions were effective in increasing milk production in post-sectio Caesarean mothers. Univariate and bivariate test analysis results obtained p-value from each test is the normality test of 0.193, homogeneity test of 0.676, and the T-test of Dependent Paired T-Test of 0,000 which means that there are significant results regarding the production of breast milk between the two test groups. In the Back-massage intervention group, the value of p-value is 0,000 <0.05, which means that milk production increases. Conclusion: Mothers who get back massage are more effective in milk production more than mothers who do not get back massage. Abstrak: Pendahuluan: Produksi ASI yang sedikit atau tidak lancar pada hari-hari pertama persalinan menjadi kendala dalam pemberian ASI bagi ibu post sectio caesarea. Pijat punggung merupakan salah satu solusi alternatif untuk mengatasi kelancaran produksi ASI. Tujuan penelitian ini adalah untuk melihat efektivitas Pijat Punggung terhadap produksi ASI pada ibu post seksio sesarea. Metode: Desain penelitian ini menggunakan dua kelompok desain pre-post-test. Populasi penelitian ini adalah seluruh 22 pasien post sectio caesarea di ruang kebidanan RSUD Waikabubak. Instrumen penelitian menggunakan angket, pedoman indikator, dan lembar observasi. Analisis data uji-t untuk data bivariat. Hasil: Hasil penelitian menunjukkan bahwa intervensi pijat punggung efektif dalam meningkatkan produksi ASI pada ibu pasca seksio sesarea. Hasil analisis uji univariat dan bivariat diperoleh p-value dari masing-masing uji yaitu uji normalitas 0,193, uji homogenitas 0,676, dan uji T Dependent Paired T- Test sebesar 0,000 yang artinya terdapat hasil yang signifikan mengenai produksi payudara. susu antara dua kelompok uji. Pada kelompok intervensi pijat punggung nilai p-value 0,000<0,05 yang berarti produksi ASI meningkat. Kesimpulan: Ibu yang mendapatkan pijat punggung lebih efektif dalam produksi ASI dibandingkan ibu yang tidak mendapatkan pijat punggung.